The Effect of Milk or its Combination with Tea and 0.2% NaF on Dental Enamel Demineralization Analyzed by Micro Computed Tomography - Rahardjo, Anton; Sahertian, Raisa D.; Ramadhani, Siti A.; Maharani, Diah A.; Latief, Fourier DE. (Journal of Dentistry Indonesia, 2014)
Fluoride and calcium play an important role in the prevention of dental caries, promoting the inhibition of demineralization and the increase of remineralization. Objective: To investigate the effects of milk with/without the combination of tea and 0.2% NaF on enamel demineralization using micro-computed tomography (microCT). Methods: The coronal parts of 40 extracted sound premolars were prepared as tooth blocks. An unvarnished occlusal surface window was created for each tooth by covering the occlusal surface with a 3x5 mm2 sticker and painting all other surfaces with an acid-resistant varnish. These blocks were randomly allocated into four groups that were immersed in remineralizing solutions for 26 minutes: Group A, milk; Group B, milk and tea; Group C, milk and 0.2% NaF; and Group D, deionized water (control). Results: After 3 days of immersion in a buffered demineralization solution at pH 4.4, micro-CT scans were taken. The mean grayscale values and the standard deviations are: 98.1 ± 24.0; 90.8 ± 9.1; 92.6 ± 21.4; 81.1 ± 20.3, respectively. The mean grayscale values were significantly different among the four groups (p